Crop production on heavily disturbed soils following crude oil remediation. (22nd January 2020) - Croat, Samantha J.; O'Brien, Peter L.; Gasch, Caley K.; Casey, Francis X.M.; DeSutter, Thomas M.
Abstract: Cropland contaminated by crude oil typically requires remediation before it can meet pre‐contaminated productivity potentials. Remediation strategies focus on removing the contaminant, but they also often alter soil properties, which affects the capacity of the land to sustain agricultural production. This research describes crop production following the remediation of crude oil contaminated soil in North Dakota, USA using two different strategies, a modified land‐farming technique and ex situ thermal desorption. Wheat ( Triticum aestivum L.) and field pea ( Pisum sativum L.) were grown in soils treated by both of those techniques, as well as mixtures of each treated soil with native topsoil. Across three growing seasons of comparisons to native topsoil, crop production was 61 ± 20% lower in the modified land‐farm soils and 52 ± 25% lower in thermal desorption‐treated soils; these yield declines were likely associated with reduced soil organic carbon levels. Notably, the soil mixtures had higher soil organic carbon levels and matched the native topsoil in both yield and protein content, suggesting that soil mixing may be a promising tool in cropland soil reclamation. Overall, these findings reinforce that crop production on reclaimed land is linked with soil properties, so long‐term reclamation success requires a holistic approach to soil management.